The neuroscience of psychopathy and forensic implications - Ling, Shichun (Psychology, crime & law, 2018)
In recent years, there has been an increase in neuroscientific research on psychopathy. This research has important forensic implications, with the potential to inform the development of new treatments, improve prediction of recidivism or future dangerousness, and reform punishment options. This selective review examines youth and adult research on the neural basis of psychopathy, and the forensic implications associated with such research. In general, neuroscience findings implicate abnormalities in prefrontal and limbic structures, including the amygdala and striatum, in the etiology of psychopathy. Child and adolescent findings are less consistent than adult findings. Forensic implications of neuroimaging findings for psychopathy are briefly discussed together with limitations and directions for future research.